Reproductive variability of the Amazon River prawn, Macrobrachium amazonicum (Caridea, Palaemonidae): influence of life cycle on egg production - Meireles, Andrea L. [UNESP]; Valenti, Wagner C. [UNESP]; Mantelatto, Fernando L. (Universidade Católica de Valparaíso, 2013)
Diverse reproductive strategies may be adopted by different species of Macrobrachium prawns, and even among different populations of the same species. The present study evaluated the influence of differences in the reproductive strategies of two geographically isolated populations of Macrobachium amazonicum, upon female fecundity, reproductive output and the chemical content of prawns and eggs. One prawn population from Para only completes its life cycle in brackish water, whereas another from Mato Grosso do Sul only inhabits freshwater. Para female prawns exhibited a larger average size and weight and produced more eggs than females from Mato Grosso do Sul. However, the Mato Grosso do Sul population produced eggs that were larger in volume than those of females from the other population. Furthermore, eggs produced by Para prawns were composed primarily of water (56%), whereas those produced in Mato Grosso do Sul were composed mostly of organic matter (80%). This difference in the eggs' chemical compositions did not apply to the chemical compositions of the females, as individuals from both sites were composed primarily of water. Mato Grosso do Sul females invested a higher amount of energy in brood formation (14% of their wet weight) than individuals from Para (only 10%). It is possible that M. amazonicum populations show a higher degree of plasticity in their reproductive activity due to habitat conditions and genetic differences. Although the brackish population produces larger individuals, and exhibits higher fecundity, the freshwater population exhibited a higher reproductive investment. These results suggest a high reproductive capacity to adapt to different environmental conditions for this species, which should be considered in the context of aquaculture activities.
Keywords: Macrobrachium amazonicum; reproductive potential; ecological plasticity; egg production; Brazil